Molecular genetic analysis of the orsellinic acid/F9775 gene cluster of Aspergillus nidulans - Sanchez, James F. (2009)
F-9775A and F-9775B are cathepsin K inhibitors that arise from a chromatin remodelling deletant strain of Aspergillus nidulans. A polyketide synthase gene has been determined to be responsible for their formation and for the simpler, archetypical polyketide orsellinic acid. We have discovered simple culture conditions that result in the production of the three compounds, and this facilitates analysis of the genes responsible for their synthesis. We have now analysed the F9775/orsellinic acid gene cluster using a set of targeted deletions. We find that the polyketide synthase alone is required for orsellinic acid biosynthesis and only two additional genes in the cluster are required for F9775 A and B synthesis. Our deletions also yielded the bioactive metabolites gerfelin and diorcinol.